Analisis Optimalisasi Website PMI Kota Tegal dalam Mendukung Donor Darah dan Donasi - Chairul Tri Mardiansyah (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
The website of Palang Merah Indonesia (PMI) Kota Tegal plays a strategic role in facilitating blood donation and supporting various humanitarian programs. This study aims to analyze the optimization of the PMI Kota Tegal website in enhancing public participation in blood donation and donations through digital platforms. A qualitative descriptive method with a case study approach was employed, incorporating observations, interviews, and documentation. Website development utilized WordPress with Elementor plugins to ensure user-friendly interfaces and interactive features. Findings indicate that while the website effectively provides essential information such as donor schedules, procedures, and donation options, further optimization is needed in content interactivity, accessibility across devices, and integration with social media. Interactive features, digital forms, and clear navigation significantly influence user engagement and satisfaction. The study highlights the importance of combining digital strategies with transparency and accountability to strengthen community trust and participation. Recommendations include regular content updates, incorporation of multimedia elements, and enhancement of online donor management features to maximize the website’s role as a communication and mobilization tool.